Synergistic Biomass-based Dual-polymer System of Cationic Guar Gum and Gum Arabic for Enhanced Retention and Drainage in Papermaking - Mingjie Tan; Weitao Zhang; Enhao Fu; Fei Yang (BioResources)
Gum arabic (GA), a natural plant-derived polysaccharide renowned for its adhesive properties, is widely utilized across various industries, particularly in papermaking. This study systematically investigated the retention and drainage performance of pulp when treated with cationic guar gum (CGG) and GA individually and further explored the development of a biomass-based dual-polymer retention and drainage aid system. The CGG-GA system outperformed single-component additives by initially forming larger flocs with CGG, which were subsequently stabilized by GA, leading to enhanced retention and drainage efficiency. Additionally, the dual-polymer system reduces the cationic demand of white water, highlighting a synergistic interaction between CGG and GA. Scanning electron microscopy (SEM) analysis revealed a more uniform floc distribution in the dual-polymer system, while physical property tests confirm improved tensile strength in handsheets. This study presents a sustainable and effective alternative to conventional retention and drainage aids, offering both environmental benefits and enhanced paper quality.